SHRIMP U–Pb phosphate dating shows metamorphism was synchronous with magmatism during the Paleoproterozoic Capricorn Orogeny. Issue 7 (3rd October 2019) - Piechocka, A. M.; Zi, J.-W.; Gregory, C. J.; Sheppard, S.; Rasmussen, B.
Abstract: Unlike many Phanerozoic orogens, where the primary effects of orogenic events can be easily determined, Precambrian orogens are commonly characterised by repeated tectonothermal events making it challenging to decipher the geological history. The Capricorn Orogen is a complex Precambrian intraplate orogen located within the West Australian Craton that has been subjected to four separate reworking tectonic events between 1820 and 900 Ma. Although direct U–Pb ages for metamorphism have been obtained for the younger events, there is only limited geochronological data for the oldest event, the 1820–1770 Ma Capricorn Orogeny. This is primarily because of multiple episodes of deformation and metamorphism overprinting and obscuring the original tectonic fabrics and destroying metamorphic chronometers. In this study, we use in situ U–Pb monazite and xenotime geochronology, from a feldspathic metasandstone, a quartz–muscovite–chlorite–garnet pelitic schist, a quartz–muscovite–tourmaline schist and a garnet–biotite–plagioclase pelitic gneiss, to obtain the first direct age constraints for metamorphism during the Capricorn Orogeny in the northern Gascoyne Province. Metamorphism was synchronous with the 1820–1775 Ma magmatism in the northern part, and possibly in the southern part, of the Gascoyne Province. Furthermore, our results hint at a late stage hydrothermal fluid event at ca 1750–1730 Ma, post-dating the magmatism in the northern Gascoyne Province.